The English language influence on journalistic discourse in French and Italian - Orešković Dvorski, Lidija (2010)
OBJECTIVES: There is undoubtedly a huge impact of the English language on the majority of European languages. That fact has been particularly obvious in the last decades. Both Italian and French used to exert similar influence on standard languages of Europe in different periods of the European history. Due to a strong economic, technological and cultural development of some English-speaking countries, primarily the United States of America and Great Britain, the English language results to be the main language donor in numerous fields (commerce, politics, science etc.), within different registers (formal/informal) and various types of discourse. It could be expected that by accepting foreign elements in their own languages, the language users assume certain traits of the foreign identity. The purpose of this paper is to carry out an analysis of the influence of the English language on contemporary French and Italian, based on the corpus of the French and Italian press. The level of tolerance towards the influence of English coud be indicative of these tendencies. METHODS: The paper is focused on the use of English elements in French and Italian journalistic texts. A special attention is given to the choice of the texts to be analysed. It is required to obtain a high level of equivalence as far as topics and genres are concerned. In order to encompass a diversity of topics, the analysis includes articles dealing with issues of global importance such as economy, world/European politics, environment etc. After having examined the empirical data, we are contrasting the share of English elements in both languages at different levels of linguistic analysis. RESULTS: The contrastive analysis has shown different extents of the English language influence in the two Romance languages. In some aspects, the French and Italian texts exhibit different ways of assimilating English elements. In many cases French authors use French lanuage material to render the concept, whereas Italian authors tend to take over foreign terms in their original form as they appear in English (French/Italian: e.g. le Conseil de stabilité financière/il Financial Stability Forum ; les principaux dirigeants/il leader ; les mesures de relance monétaire et budgetaire/exit strategy, le manovre anti-recessive ; une croissance durable/la crescita sostenibile ; le sommet/il summit..............) CONCLUSIONS: The impact of the English language is evident at all levels of linguistic analysis. It is presumed that the intention of news story writers to render the atmosphere and spirit of the internationally relevant events contributes to the extent to which English elements occur in texts, which can have further effects related to the entrechment of loan words in the lexical inventory of the two languages. Presuming that the target audience of the analysed texts are predominantly standard language speakers, it could be expected that the observed phenomena might have further repercussions on spreading of the English influence. KEY WORDS: contrastive analysis, French, Italian, English langage, journalistic discourse